A Study on The Adoption of Autonomous Online Shopping from The Perspective of Customer Trust and Perceived Risk - Mohd Khir, Nur Syuhada; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
The advancement of technology including Artificial Intelligence (AI), machine learning, robots and many more has made more consumers move towards modernization where most of technology focuses on the automation. This in line with rapid growth of technology, where most of countries invest huge amount of money to come up with an innovation. Currently, autonomous systems are getting more attention and are being implemented in every sector, especially the retail industry. Because it is a new technology, there are still few studies that explore the adoption of autonomous shopping systems in the context of online shopping. However, studies on an autonomous online shopping system still very lacking of follower’s perspectives especially in context of Gen Y and Gen Z. Hence, this research aims to find a relationship between trust and perceived risk in autonomous shopping systems and online shopping intention in context among Gen Y and Gen Z. This study has collected data from 155 respondents among Gen Y and Gen Z in Johor. Data will be collected using quantitative data using a questionnaire survey. All the collected data were analyzed using the Statistical Package for Social Science (SPSS) to expand the quantitative reports presented in frequency, percentage of mean, and standard deviation. This study assists businesses understand and implement business strategy. The result shows all variables have a significant relationship with online shopping intention and trust has the highest correlation coefficient of 0.677.